Pointing out persuasion in Philemon: fifty readings of Paul's rhetoric from the fourth to the Eighteenth Century - Tolmie, D. F. (History of biblical exegesis, 2021)
Cover -- Title -- Preface -- Table of Contents -- Abbreviations -- Introduction -- Chapter 1: The Wirkungsgeschichte of the Rhetoric of the Letter to Philemon in the Early Church -- 1. Ambrosiaster -- 2. Jerome -- 3. John Chrysostom -- 3.1 Argument -- 3.2 Homily 1 -- 3.3 Homily 2 -- 3.4 Homily 3 -- 3.5 Evaluation -- 4. Pelagius -- 5. Theodore of Mopsuestia -- 6. Theodoret of Cyrus -- 7. Cassiodorus -- 8. John of Damascus -- Chapter 2: The Wirkungsgeschichte of the Rhetoric of the Letter to Philemon in the Middle Ages -- 1. Alcuin of York -- 2. Claudius of Turin -- 3. Hrabanus Maurus -- 4. Haimo of Auxerre -- 5. Florus of Lyon -- 6. Isho'dad of Merv -- 7. Sedulius Scottus -- 8. Pseudo-Oecumenius -- 9. Atto of Vercelli -- 10. Lanfranc of Bec -- 11. Bruno the Carthusian -- 12. Theophylact of Ohrid -- 13. Euthymius Zigabenus -- 14. Commentarius Cantabrigiensis -- 15. Glossa Ordinaria -- 16. Peter Lombard -- 17. Hervaeus of Bourg-Dieu -- 18. Thomas Aquinas -- 19. Pierre de Tarentaise -- 20. Nicholas of Lyra -- 21. Denys the Carthusian -- Chapter 3: The Wirkungsgeschichte of the Rhetoric of the Letter to Philemon from the Sixteenth to the Eighteenth Century -- 1. Desiderius Erasmus -- 2. Johannes Bugenhagen -- 3. Martin Luther -- 4. Thomas de Vio Cajetan -- 5. Heinrich Bullinger -- 6. Johannes Brenz -- 7. John Calvin -- 8. Theodore Beza -- 9. Georg Major -- 10. Lambert Daneau -- 11. William Attersoll -- 12. Cornelius a Lapide -- 13. Gulielmus Estius -- 14. John Mayer -- 15. Hugo Grotius -- 16. David Dickson -- 17. John Trapp -- 18. Abraham Calovius -- 19. Matthew Henry -- 20. Georg Michael Laurentii -- 21. Johann Albrecht Bengel -- 22. Siegmund Jacob Baumgarten -- Chapter 4: Conclusion. Tendencies in the Interpretation of Paul's Rhetorical Strategy in the Letter to Philemon over the Centuries -- 1. Imagining the Rhetorical Situation.